Introduction to the theory of earthquakes - Apostol, Bogdan Felix (New Delhi : Cambridge International Science Publishing, 2022)
This little book is a brief introduction to the main themes of the earth-quakes physics described more extensively in author's larger book Theory of Earthquakes. Both books are motivated by the need felt by the author that earthquakes physics deserves a treatment carried with the more adequate and powerful methods of the theoretical physics, in particular the theory of elasticity and equations of mathematical physics. Such a treatment is not to be found in the current seismological literature; this literature is motivated by authors knowledge of solving certain problems, not by real physical phenomena related to earthquakes.
Keywords: Earthquakes; Elastic wave theory; Seismic waves; Tensor analysis